Comparison of the Effects of Static-Stretching and Tubing Exercises on Acute Shoulder Range of Motion in Collegiate Baseball Players - Andrew M Busch; Jackson Browstein; Richard Ulm (North American Sports Medicine Institute, 2021)
# Background The overhead throwing motion repetitively stresses the dominant arm in baseball players, frequently altering normal range of motion (ROM) in multiple directions. Baseball players regularly perform a combination of static stretches (SS) and dynamic tubing (DT) resistance exercises in pre-throwing warm-up routines intended to improve shoulder ROM and reduce injuries. # Purpose The purpose of this study was to compare acute changes in dominant shoulder ROM improvements between SS and DT warm-up exercise protocols. The DT exercises were hypothesized to elicit greater improvements in shoulder ROM. # Study Design Two-way crossover study. # Methods Twenty-five healthy collegiate baseball players (mean age = 19.8 ±1.0 years) presenting with glenohumeral internal rotation deficit (GIRD) >20° and total rotational range of motion (TRROM) losses >5° completed the SS and DT interventions on different days. Dominant arm internal rotation (IR), external rotation (ER) and TRROM were measured before, immediately after, 30-minutes after, and 60-minutes after each treatment session. A two-way repeated measures analysis of variance (ANOVA) compared the effect of SS and DT over time on IR, ER and TRROM. # Results IR improved on average 10.68 ± 0.82° (p < .001) post intervention, 11.18 ± 0.79° (p < .001) 30-min post intervention, and 9.03 ± 0.95° (p < .001) 60-min post intervention. ER improved on average 8.60 ± 0.67° (p < .001) post intervention, 8.25 ± 0.85° (p < .001) 30-min post intervention, and 6.65 ± 0.91° (p < .001) 60-min post intervention. TRROM improved on average 19.28 ± 1.09° (p < .001) post intervention, 19.43 ± 1.36° (p < .001) 30-min post intervention, and 15.68 ± 1.55° (p < .001) 60-min post intervention. There were no significant differences between the main effects of treatment and time for IR, ER, and TRROM. For IR, SS improved by an average of 1.73 ± 0.55° (p = .005) more than DT. For ER and TRROM, there were no differences between SS and DT. # Conclusion Both SS and DT exercises improve glenohumeral IR, ER and TRROM up to one-hour post intervention, with no significant differences noted between interventions for treatment or time. Baseball players can benefit equally from performing SS or DT exercises to acutely improve shoulder ROM. # Level of Evidence Level 3